PENEBUSAN KRISTUS DALAM TULISAN PAULUS DAN EVALUASI TERHADAP PENEBUSAN DALAM PLURALITAS AGAMA DI ASIA - Herry Purwantoro; Fonny Elvira Ester Laoh (Jurnal Sarita Bahalap, 2025)
ABSTRACT Theology is taught by God, teaches about God, and must lead humanity back to God. Every effort to understand and formulate theology must be studied and tested within the framework outlined above. The Bible is God's revelation given to humanity through a written process inspired by the Holy Spirit. The Bible was given primarily so that humanity might believe that Jesus is the Messiah, the Son of God, and that through faith, humanity might have life in His name (John 20:31). Hermeneutics, as an interpretive system for understanding the Bible, will determine the resulting understanding. The presupposition that the Bible is the revealed word of God will produce a different understanding than the presupposition that the Bible is ancient literature that must be understood through a critical sociological-anthropological approach. To study and initiate Redemption within religious pluralism in Asia, researchers base their research on a hermeneutical system that believes the Gospel (Bible) is inspired by the Holy Spirit. Because only the Holy Spirit enabled the disciples to understand Jesus of Nazareth in a proportional way. It was also the Holy Spirit who guided the writing of the Gospels and who opened the hearts of believers today to understanding. Therefore, through the Holy Spirit, the knowledge of Jesus of Nazareth by the Gospel writers and by Christians today is the same. There is no need for a separation between the Jesus of history and the Jesus of faith, because knowing the Jesus of history is identical to knowing the Jesus of faith. The evaluation results indicate that the atonement within Asia's religious plurality is based on a theological hermeneutical system that rejects the inspiration of the Holy Spirit in the writing of the Bible and employs a sociological-anthropological approach to its interpretation. Nevertheless, this approach represents a careful contextualization effort that should be viewed positively, even though it involves a dismantling of fundamental Christian doctrines. Keywords: Atonement, Evaluation. ABSTRAK             Teologi adalah diajar oleh Allah, mengajar tentang Allah, dan harus membawa manusia kembali kepada Allah. Setiap upaya memahami dan merumuskan teologi, harus dikaji dan diuji dengan  frame-work di atas. Alkitab adalah penyataan Allah yang diberikan kepada manusia melalui proses penulisan dalam inspirasi Roh Kudus. Alkitab diberikan terutama supaya melaluinya manusia percaya bahwa Yesus adalah Mesias Anak Allah, dan supaya oleh imannya, manusia memperoleh hidup dalam nama-Nya (Yohanes 20:31). Hermeneutika sebagai sistem penafsiran untuk memahami Alkitab, dalam penggunaannya akan menentukan bentuk pemahaman yang dihasilkan. Presuposisi bahwa Alkitab adalah firman Allah yang diwahyukan, akan menghasilkan pemahaman yang berbeda dengan presuposisi bahwa Alkitab adalah sastra kuno yang perlu dipahami melalui pendekatan kritis sosiologis-anthropologis.             Untuk mengaji dan mengevaluasi Penebusan dalam pluralitas agama di Asia, peneliti mendasarkannya pada sistem hermeneutika yang meyakini bahwa Injil (Alkitab) diinspirasi Roh Kudus. Karena hanya Roh Kuduslah yang menjadikan para murid dapat memahami secara proporsional, Yesus dari Nazareth. Roh Kudus pula yang membimbing dalam proses penulisan Injil, dan yang membuka hati orang percaya pada masa kini untuk mengerti. Oleh karena itu, melalui Roh Kudus, pengenalan akan Yesus dari Nazareth oleh para penulis Injil dan orang Kristen masa kini adalah sama. Tidak perlu ada pemisahan antara Yesus sejarah dan Yesus iman, karena pengenalan akan Yesus sejarah identik dengan pengenalan akan Yesus iman.             Hasil evaluasi menunjukkan bahwa penebusan dalam pluralitas agama di Asia didasarkan pada sistem hermeneutika teologi yang menolak inspirasi Roh Kudus dalam proses penulisan Alkitab, dan menggunakan pendekatan sosiologis-anthropologis dalam penafsirannya. Kendati demikian, pendekatan yang dilakukan merupakan upaya kontekstualisasi yang cermat, yang perlu disikapi secara positif, kendati dilakukan dengan meleburkan doktrin dasar Kekristenan. Kata kunci: Penebusan, Evaluasi.